Circadian phase-specific degradation of the F-box protein ZTL is mediated by the proteasome - Kim, Woe-Yeon (National Academy of Sciences, 2003)
Critical to the maintenance of circadian rhythmicity is the cyclic expression of at least some components of the central oscillator. High-amplitude cycling of mRNA and protein abundance, protein phosphorylation and nuclear/cytoplasmic shuttling have all been implicated in the maintenance of circadian period. Here we use a newly characterized Arabidopsis suspension cell culture to establish that the rhythmic changes in the levels of the clock-associated F-box protein, ZTL, are posttranscriptionally controlled through different circadian phase-specific degradation rates. This proteolysis is proteasome dependent, implicating ZTL itself as substrate for ubiquitination. This demonstration of circadian phase-regulated degradation of an F-box protein, which itself controls circadian period, suggests a novel regulatory feedback mechanism among known circadian systems.